AI and the Future of Work: Threat or Opportunity? (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the role of Artificial Intelligence (AI) has become one of the most influential technological innovations shaping the future of employment, generating extensive debate regarding its potential to function as either a source of labor displacement or a catalyst for workforce development. This study aims to analyze the dual implications of AI for the future of work by examining employment restructuring, workforce adaptation, and governance challenges associated with intelligent technologies. The research employs a non-empirical design based on a structured literature review and integrative analytical framework that synthesizes insights from labor economics, digital transformation studies, innovation research, and workforce adaptation theories. The findings indicate that AI transforms labor markets by automating selected tasks while simultaneously creating new professional opportunities and enhancing organizational productivity. The analysis further demonstrates that workforce resilience increasingly depends on digital literacy, continuous learning, critical thinking, and adaptive competencies capable of complementing intelligent systems. Governance issues, including algorithmic bias, workplace surveillance, accountability, and inequality, emerge as critical determinants of sustainable technological integration. The study concludes that the future impact of AI is contingent upon effective collaboration among governments, industries, educational institutions, and society to ensure inclusive, ethical, and sustainable employment transformation in the digital era.